To connect between worlds, to bridge over gaps: learning about the complex role of cultural mediators in perinatal health promotion from a case in Israel - Hagit Peres; Rachel Sharaby (BMC, 2020)
Abstract Background Reduction of health gaps between ethno-cultural groups has become a major concern for health services, with a strong emphasis on eliminating social and cultural barriers and improving accessibility for diverse populations. Methods The study is based on a Participatory Action Research where an involved researcher accompanied the project for a decade, as well as on eleven in-depth interviews with Bedouin women-mediators working in a perinatal health promotion project in Israel. Results The research analyzes the work of Bedouin women health mediators who mediate between their Bedouin community and institutional health services and bridge over cultural gaps. The study presents the complex task of transferring messages across cultures, dealing with socio-cultural imperatives and the intricacy of multilayered power relations. The findings reveal an evolving process, beginning with a pragmatic mediation model in which the mediators are limited to instruction of pre-defined health materials, toward a transformative model of creating a ground for encouraging the mediators to act creatively according to socio-cultural circumstances. Conclusion The research elaborates on the adoption and implementation of the transformative approach in mediation and provides further understanding of the complexity of mediation role in sensitive issues such as pregnancy, birth and infant care.